Analisis Framing Drama Korea “Pyramid Game ” sebagai Gambaran Hierarki Sosial Remaja Korea Selatan - Devi Cindy Claudya Simanjuntak; Angel Damayanti; Silvia Nevane Paramasi (Jurnal Cakrawala Akademika, 2025)
Facing the era of information globalization and technological developments, the world is finally facing a rapid change in the flow of information. This is one of the drivers to change the way people think about getting information quickly, accurately and reliably. This research uses a qualitative approach where the qualitative research approach is an activity that places observers in the real world. The type of research used in this study is the descriptive research type. This research will use the method of using the observation method by systematically observing and recording the drama shows.""Pyramid Game" centers on the lives of high school students who follow a social game system called "Pyramid Game". The results show that the Pyramid Game frames the social hierarchy of adolescents as a structural problem that is maintained by social pressures, a competitive culture, and an education system that emphasizes ranking. The main problem is defined as the injustice in the school's social system that normalizes bullying. The cause is described as a social structure that allows power to be determined by popularity. This drama assesses this condition as a form of immoral systemic oppression. The solutions offered are the need for individual and collective awareness to reject harmful systems and build a more just and empathetic social environment. The drama effectively conveys a social critique of the realities faced by South Korean teenagers, as well as inviting the audience to reflect again on the importance of the values of equality, empathy, and social change.